Analysis of the Mechanism for Selecting Organizational and Technological Solutions for Integrated Management of Construction Processes - Ichetovkin, A. O. (Science and Transport Progress, 2023)
Purpose. The main purpose of this article is to thoroughly substantiate the possibilities of implementing a mechanism for selecting organizational and technological solutions to achieve parametric criteria for managing construction processes, especially under conditions of uncertainty. To achieve this goal, we use a functional model of the system-integrated approach, which allows us to systematize and coordinate management functions at the level of individual processes. Methodology. The study is based on the introduction of new requirements for standardization in the construction industry, in particular, on the use of the parametric method. This method can improve management strategies, methods, and technologies, as well as facilitate the implementation of innovative organizational and technological solutions. As a result, the quality and volume of construction can be improved, which, in turn, will help overcome the crisis and develop the construction industry. The management process involves achieving a key goal, namely the efficiency of project implementation, while construction has certain specifics that complicate the management process and require the use of more complex, integrated, and multi-directional organizational and technological solutions. Findings. In the current economic environment, which provides for both an increase in the number of risks in the construction sector and the size of their possible consequences, in the context of increasing (expanding the list) of quality requirements for construction projects, there is a reasonable need to search for and improve organizational and technological solutions in order to apply new approaches to the management of construction processes related to the practical implementation of the results of modern scientific and methodological research. The results obtained, however, indicate that the use of the parametric method creates new challenges for the efficiency of management in the construction industry. The increased number of management decision alternatives, identification of risks and improvement of consequence forecasting processes may cause certain difficulties. On the other hand, the lack of clear requirements can lead to increased costs and risks. Originality. The paper substantiates the necessity of using a system-wide algorithmic mechanism for the effective management of construction processes under conditions of uncertainty. This is important for adapting to modern challenges and ensuring the sustainable development of the construction industry. Practical value. The study makes it possible to determine the compliance of organizational and technological solutions with the established criteria and compare them to select the most effective one, in particular in terms of cost, efficiency and risk mitigation.